Consensus statements on optimal adult post-autism diagnosis support and services: Delphi process following a UK survey of autistic adults, relatives and clinicians. (February 2023) - Wigham, Sarah; Ingham, Barry; Le Couteur, Ann; Wilson, Colin; Ensum, Ian; Parr, Jeremy R
Opportunities for adults to access support following a clinical diagnosis of autism are limited. This study investigated perspectives of autistic adults, relatives and clinicians regarding characteristics of optimal adult autism post-diagnosis support and services. In Stage 1, key stakeholders were surveyed about recent experiences of UK adult autism post-diagnostic services immediately following assessment/up to 12 months afterwards. Information gathered from Stage 1 was used to devise a set of statements describing optimal post-autism diagnostic support/service characteristics. In Stage 2 statements were presented to clinicians in a modified Delphi process. Data analyses were non-parametric and descriptive. Three hundred forty-three autistic adults and 45 relatives completed the Stage 1 surveys. Thirty-five clinicians completed a parallel survey. Just over half of adults and relatives reported receiving a follow-up appointment. Fewer than 40% of autistic people received support/services 12 months after diagnosis. Eleven statements describing optimal post-autism diagnostic support/service provision were developed and consensus among clinicians was reached on all. Autistic adults, relatives and clinicians described some aspects of post-autism diagnosis support and services positively; however, there were significant opportunities for improvement. The study findings can be used to develop current UK post-diagnosis support and services and may be relevant internationally. Lay Abstract: Research has identified types of support helpful to autistic people, for example, physical and mental health interventions, psycho-education, peer support, developing positive identities and affiliation with social groups. However, accessing suitable post-autism diagnosis support and services is extremely difficult. We asked autistic adults, relatives and clinicians about their experiences of receiving and delivering post-autism diagnosis support/services. In Stage 1, 343 autistic adults and 45 relatives completed a survey. They answered questions about their experiences of UK autism post-diagnosis support/services for adults within 12 months after receiving a diagnosis. Thirty-five clinicians completed a similar survey. Just over half of adults and relatives said there was a follow-up appointment or discussion about support after diagnosis. Fewer than 40% received any support/services in 12 months after diagnosis. We used information from the surveys to create 11 statements describing characteristics of appropriate adult post-autism diagnosis support/services. In Stage 2, we asked clinicians for their views on the statements – they agreed with all of them. For example, those adults are offered an additional follow-up meeting after diagnosis and have access to mental and physical health services. We shared results with autistic adults, relatives and clinicians at two events. Some autistic adults, relatives and clinicians were positive about post-autism diagnosis support/services. However, they described many areas for improvement. The study findings can be used to define, develop and improve the types of adult post-diagnosis support services.